The impact of creditor protection on stock prices in the presence of liquidity crises: Theory and cross-country evidence - Galina Hale; Assaf Razin; Hui Tong (Center for Economic Studies and ifo Institute (CESifo), 2012)
We develop a model predicting two channels through which creditor protection enhances the performance of stock prices: (1) The probability of a liquidity crisis leading to a binding investment-finance constraint falls with a strong protection of creditors; (1) The stock prices under the investment-constrained regime increase with better protection of creditors. We find empirical support for both predictions using data on stock market performance, amount and cost of credit, and creditor rights protection for 52 countries over the period 1980-2008. In particular, we find that better creditor protection is correlated across countries with lower average stock market volatility, crises are more frequent in countries with poor creditor protection. Using propensity score matching we also show that during crises stock market returns and investment fall by more in countries with poor creditor protection.
Keywords: E44; 330; liquidity crisis; creditor protection; stock volatility; credit crunch; Gläubigerschutz; Aktienmarkt; Börsenkurs; Volatilität; Finanzmarktkrise; Marktliquidität; OECD-Staaten